Effect of dietary 25-hydroxycholecalciferol supplementation and high stocking density on performance, egg quality, and tibia quality in laying hens - Wang, Jianping (Poult Sci, 2020)
This study was conducted to determine the effects of 25-hydroxycholecalciferol (25-OH-D(3)) on performance, egg quality, tibia quality, and serum hormones concentration in laying hens reared under high stocking density. A total of 800 45-week-old Lohmann laying hens were randomly allotted into a 2 × 2 factorial design with 2 levels of dietary 25-OH-D(3) levels (0 and 69 μg/kg) and 2 rates of stocking densities [506 (low density) and 338 (high density) cm(2)/hen]. Laying hens were monitored for 16 wk. High stocking density decreased laying rate, egg weight, and feed intake compared with low stocking density (P < 0.01) during 1 to 8 wk and 1 to 16 wk. Overall, high stocking density increased eggshell lightness value and decreased shell redness and yellowness value, strength, thickness, and relative weight compared with low stocking density (P < 0.05). Dietary supplementation with 25-OH-D(3) reduced the value of the eggshell lightness and increased its yellowness and eggshells weight (P ≤ 0.05). The increase in eggshell thickness was more pronounced when 25-OH-D(3) was supplemented to layers under high stocking density (interaction, P < 0.05). Layers under high stocking density had lower ash content and calcium content in the tibia than layers under low stocking density (P = 0.04); dietary 25-OH-D(3) increased tibia strength compared with no addition (P = 0.05). Layers under high stocking density had higher serum concentrations of 25-OH-D(3), corticosterone (CORT), lipopolysaccharide (LPS), and osteocalcin (OC; P < 0.05), lower content of parathyroid hormone (PTH) compared with layers under low stocking density (P < 0.01). Dietary 25-OH-D(3) increased serum concentration of 25-OH-D(3), carbonic anhydrase (CA), and calcitonin (CT) (P < 0.01) and reduced corticosterone, lipopolysaccharide and osteocalcin concentration (P ≤ 0.05). The increase effect in PTH was more pronounced when 25-OH-D(3) was supplemented to layers under high stocking density (interaction, P = 0.05). Overall, the results gathered in this study indicate that high stocking density result in reducing production performance, shell color and quality, and tibia health, whereas dietary 25-OH-D(3) was able to maintain tibia health and to mitigate the negative impact of high stocking density on productive performance.